2006
DOI: 10.4314/eamj.v83i4.9417
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of trachoma in six districts of Kenya

Abstract: Objectives:To estimate the prevalence of active trachoma (TF) in children aged one to nine years and potentially blinding trachoma (TT) in adults aged 15 years and older in six known trachomaendemic districts in Kenya. Design: Community based survey. Setting: Six known trachoma endemic districts in Kenya (Samburu, Narok, West Pokot, Kajiado Baringo and Meru North). Subjects: A total of 6,982 children aged one to nine years and 8,045 adults aged 15 years and older were randomly selected in a two stage random cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…Fig 4 shows data taken from published PBPSs in Nigeria [3844], Niger [45], Sudan [46], Kenya [16], Ethiopia [47] and Cameroon [48,49] comparing the prevalence of TF in those aged 1–9 years with the prevalence of TT in 15+ year-olds in the same EUs, all of which were treatment-naïve. Of 58 identified EUs with comparable prevalence of TF in the 1–9 year olds (10% < TF < 40%) to that observed in the current study, 50% had a TT prevalence greater than 1% in those over the age of 15 years; the median TT prevalence was 1%, compared to 0.1% in our survey.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig 4 shows data taken from published PBPSs in Nigeria [3844], Niger [45], Sudan [46], Kenya [16], Ethiopia [47] and Cameroon [48,49] comparing the prevalence of TF in those aged 1–9 years with the prevalence of TT in 15+ year-olds in the same EUs, all of which were treatment-naïve. Of 58 identified EUs with comparable prevalence of TF in the 1–9 year olds (10% < TF < 40%) to that observed in the current study, 50% had a TT prevalence greater than 1% in those over the age of 15 years; the median TT prevalence was 1%, compared to 0.1% in our survey.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that TF prevalence was above the WHO-recommended threshold (≥10% TF in children aged 1–9 years) for public health interventions in the Melanesian-dominated districts studied (Solomon Islands and Fiji). Those surveys also reported surprisingly low levels of TT [12,13] (at or below the WHO elimination threshold of 0.1% in the all-ages population[14]) compared to those observed in other populations with highly prevalent TF [15,16]. …”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that when district prevalence rates are just above 10% (say between 10% and 15%) rapid assessment village by village in the district may be appropriate to identify which villages need mass treatment, which may get just targeted treatment and which may be stopped for treatment altogether. Such district level variation is not unique, and has been reported in a recent study in Kenya (Karimurio et al, 2006) It is also worth noting that none of the villages in Kongwa, and only two in Manyoni, had a complete absence of infection in the children sampled. While in general, infection rates were low when trachoma rates were low, it was not altogether absent.…”
Section: Discussionmentioning
confidence: 90%
“…The findings from the previously surveyed districts have been published in peer reviewed journals 5 6. The six surveys were conducted in line with the WHO guidelines for trachoma managers1 and the standard age range of ≥15 years was adopted 8.…”
Section: Methodsmentioning
confidence: 99%
“…Providing TT surgical procedures is also challenging 4. In Kenya, about 1300 TT procedures were being performed annually against an established backlog of 45 000 people with TT 5 6…”
Section: Introductionmentioning
confidence: 99%